A Prospective Study on the Association Between Grip Strength and Cognitive Function Among Middle-Aged and Elderly Chinese Participants - Liu, Yong; Cao, Xinyi; Gu, Nannan; Yang, Bixi; Wang, Jijun; Li, Chunbo (Frontiers in Aging Neuroscience, 2019)
Objective: To study the efficacy of grip strength (GS) as a predictor of cognitive function in a large, nationwide sample of Chinese participants aged 45 years and above. Methods: We used data from three waves (W1, W2, and W3) fielded by the China Health and Retirement Longitudinal Study (CHARLS). Cognitive function was tested biennially and calculated using two categories: episodic memory and mental intactness. Demographics, health behaviors, and medical conditions were considered potential confounders. Using multivariate linear regression models, we examined the association between baseline GS (measure in W1) and cognitive function in W3. Using a generalized estimating equation, we examined baseline GS as predictor of cognitive function change. Results: Total 9,333 individuals (53.2% women), with a mean baseline episodic memory score of 6.5, mean baseline mental intactness score of 7.7, and aged over 45 years (mean age=58.6), were selected. The mean follow-up time was 4.0 years (range: 3.3-5.0 years). Using multivariate linear regression models and comparing the lowest GS score with the highest baseline GS score, we observed significant correlation with a higher global cognitive function in both women (β=1.061, p<0.001) and men (β=1.233, p<0.001). After adjusting baseline global cognition, the highest GS level was still statistically significant in both women (β=0.543, p<0.05) and men (β=0.702, p<0.005). Generalized estimating equation suggested that the participants in the highest GS quartile had a better cognitive performance over time in both women (β=0.116, p=0.030) and men (β=0.143, p=0.008) than those in the lowest quartile. Conclusions: Higher baseline level of GS was significantly related to better cognitive function and slowed the rate of its decline. Thus, it is an independent predictor of better cognitive status in middle-aged and elderly Chinese.